Estimates for bilinear approximations of the classes TeX of periodic functions of two variables - Solich, K. V. (Ukrains’kyi Matematychnyi Zhurnal, 2012)
We obtain exact-order estimates for the best bilinear approximations of the classes $S_{p, θ}^{Ω} B$ of periodic functions of two variables in the space $L_q$ for some relations between the parameters $p, q, θ$.